Activation of the coagulation cascade in patients with leptospirosis. - Chierakul, W; Tientadakul, P; Suputtamongkol, Y; Wuthiekanun, V; Phimda, K; Limpaiboon, R; Opartkiattikul, N; White, N; Peacock, S; Day, N (2008)
BACKGROUND: Disseminated intravascular coagulation (DIC) is common among patients with sepsis. Leptospirosis is an important cause of sepsis in tropical areas, and pulmonary hemorrhage associated with thrombocytopenia is the major cause of death, but the coagulopathy in severe leptospirosis has not been further characterized. The aim of this study was to evaluate coagulation factors and the presence of DIC in patients with leptospirosis in northeast Thailand. METHODS: We measured plasma concentrations of fibrinogen, D-dimer, thrombin-antithrombin III complexes, and prothrombin fragment 1,2 and evaluated the DIC score in 79 patients with culture-confirmed and/or serologically confirmed leptospirosis and in 33 healthy Thai control subjects. RESULTS: The median concentrations of fibrinogen, D-dimer, thrombin-antithrombin III complexes, and prothrombin fragment 1,2 were significantly elevated in a cohort of 79 patients with leptospirosis, compared with healthy control subjects (P